Telecommunications and Security Reform - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2017)
The Telecommunications Association is hosting a two day forum in Melbourne in mid-November 2017 on telecommunications and security. With the Parliament passing legislation in support of the government’s telecommunications sector security reforms agenda there is a timely need to explore the legislation and to identify what the immediate outcomes will be for the telecommunications sector. With only 12 months to prepare before the new regime kicks in the TelSoc forum provides an opportunity for discussion on this key topic. Papers in this issue of the Journal cover a range of topics that cover historical events, book reviews and international telecommunications markets including a unique look at the development of the telecommunications market in Indonesia.